2013
DOI: 10.2522/ptj.20110463
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Experience Enhances Physical Therapist Student Confidence in Managing a Patient in the Critical Care Environment

Abstract: Incorporating a simulated, interprofessional critical care experience into a required clinical course improved physical therapist student confidence in technical, behavioral, and cognitive performance measures and was associated with high student satisfaction. Using simulation, students were introduced to the critical care environment, which may increase interest in working in this practice area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
98
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(120 citation statements)
references
References 50 publications
10
98
1
Order By: Relevance
“…18 It was also suggested that the use of HFMS provides students the opportunity to practice communication, critical thinking, clinical decision-making, and technical skills in a safe but realistic environment. 6,8,11,[18][19][20] Our research supports these findings and suggests that students can develop skills within the affective domain of learning that are not often as easily developed in a formal educational setting. 21 Racchini et al 22 suggest the use of a debriefing session when using HFMS to provide the students an opportunity to reflect on the scenario and consider it as an important aspect to the simulation experience.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…18 It was also suggested that the use of HFMS provides students the opportunity to practice communication, critical thinking, clinical decision-making, and technical skills in a safe but realistic environment. 6,8,11,[18][19][20] Our research supports these findings and suggests that students can develop skills within the affective domain of learning that are not often as easily developed in a formal educational setting. 21 Racchini et al 22 suggest the use of a debriefing session when using HFMS to provide the students an opportunity to reflect on the scenario and consider it as an important aspect to the simulation experience.…”
Section: Discussionsupporting
confidence: 72%
“…Although these forms of training are effective, the use of high-fidelity manikin simulation (HFMS), such as SimMan3G (Laerdal Medical Canada), in the training of health care professionals has been shown to increase advanced cardiac life support (ACLS) knowledge, knowledge retention, and overall confidence compared with the above traditional forms of training. 1 In pharmacy, 4 chiropractic, 7 and physiotherapy 8 education, simulation in critical care and clinical care settings has been shown to enhance confidence in students and increase student satisfaction with learning, and students have indicated that simulation was an extremely valuable tool for their education. 10 Including the use of simulation in the medical curriculum improved the quality of care by residents in ACLS situations, and it was their recommendation that simulation be used as a complement to traditional education.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have evaluated the impact of HPS on physiotherapy students' confidence (Ohtake et al, 2013;Smith et al, 2012), and satisfaction (Smith et al, 2012) in a cardiopulmonary setting, and found it to be an effective education tool. This study has demonstrated that students are motivated to participate in HPS in a variety of physiotherapy settings, and at an early stage of their education.…”
Section: Discussionmentioning
confidence: 99%
“…Simulation based learning (SBL) consists of both a "hands-on" experience of a mock-clinical event or situation and a debrief session of reflection and feedback (Shinnick, Woo, & Mentes, 2011). Whilst relatively new in physiotherapy curricula and with few publications (Mori, Carnahan, & Herold, 2015;Ohtake, Lazarus, Schillo, & Rosen, 2013;Smith, Prybylo, & Conner-Kerr, 2012), human patient simulation (HPS) is used in many countries across various medical (Barsuk, Cohen, Feinglass, McGaghie, & Wayne, 2009;Evans et al, 2010;Issenberg, McGaghie, Petrusa, Lee Gordon, & Scalese, 2005;Morgan, Cleave-Hogg, McIlroy, & Devitt, 2002;Steadman et al, 2006;Zendejas, Wang, Brydges, Hamstra, & Cook, 2013) and nursing programs (Ballangrud, Hall Lord, Hedelin, & Persenius, 2013;Davis, Kimble, & Gunby, 2014;Garrett, MacPhee, & Jackson, 2010;Ironside, Jeffries, & Martin, 2009;Johannesson, Silén, Kvist, & Hult, 2013;Shinnick et al, 2011;Traynor, Gallagher, Martin, & Smyth, 2010), with various measures of outcome. These activities provide students with opportunities to perform treatment on a realistic patient (rather than a peer) in an environment similar to that they will experience in actual clinical practice.…”
Section: Introductionmentioning
confidence: 99%